POTTERY AT OSTIA (4TH TO 8TH CENTURIES) THE EVIDENCE FROM THE AAR-DAI EXCAVATIONS - Martin, Archer (Rei Cretariae Romanae Fautorum Acta, 2024)
Between 1998 and 2001 the Deutsches Archäologisches Institut Rom and the American Academy in Rome carried out a series of small sondages throughout the previously unexcavated areas of Ostia as a follow-up to geophysical surveying, which gave a very detailed plan. The aim of the project was to clarify the urbanistic development of the city, and the excavation was designed to provide dating for key points rather than to discover significant ceramic contexts. Never- theless, the material found can shed light on Ostia, particularly for the later periods, the evidence for which was discarded in the great excavation campaigns of the first half of the 20th century AD: the finds themselves indicate the evolution of Ostia’s pottery supply from late antiquity to the early Middle Ages and their distribution suggests a progressive contraction of the inhabited area of the city.